Implementasi Rekam Medis Elektronik Dan Kajian Hukumnya - M.Sholkhan (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
Nowadays information technology is developing very rapidly in the health sector. As technology advances, the use of medical records has begun to shift from conventional or paper-based to digital. Electronic medical records (EMR) are an important part of health services. Electronic medical records are electronic information created by health care providers based on patient conditions, forwarded and sent to other departments for consultation and further examination and received and stored in digital form and can be viewed at any time if needed. Electronic medical records are very useful for healthcare organizations, healthcare professionals as well as patients. The purpose of this study was to analyze the implementation of electronic medical records and legal studies. This study used normative juridical research methods. This study had a specificity, namely descriptive-analytic where this study sought to analyze legal issues and also the legal system, that it could be understood and then conclusions could be drawn. The results showed that the implementation of electronic medical records, namely first, the implementation of electronic medical records could increase the accuracy and security of data. Second, the implementation of electronic medical records could increase efficiency and productivity. Third, the implementation of electronic medical records could provide better service to patients. The legal basis for implementing electronic medical records was contained in the Regulation of the Minister of Health Number 269/MENKES/PER/III/2008 concerning Medical Records where in Article 2 Paragraph (2) it was explained that "Medical records must be written, complete and clear or electronic". ITE Law Number 19 of 2016 did not regulate how electronic medical records were issued. Electronic medical records as a form of medical document must comply with applicable legal requirements, such as the right to privacy, confidentiality, accuracy and data security. It was hoped that legal certainty in the implementation of electronic medical records could help improve and improve health services.